The Relationship Between Diabetes Burnout and Quality of Life: The Mediating Role of Glysemic Control - Özden, Gürkan; Aktura, Seher Çevik; Ceviz, Ahmet (Ege Üniversitesi, 2025)
Objective: The aim of this study was to investigate the effects of burnout levels on quality of life and glycemic control in patients diagnosed with type 2 diabetes. In particular, the impact of burnout on HbA1c levels, glycemic control and general health status of patients was to be determined and the relationship between burnout level and quality of life assessed. Methods: The study was conducted with a descriptive and correlative design in the endocrine department of a college hospital in eastern Turkey between January and March 2024. The study included 168 patients who were over 18 years of age, had been diagnosed with type 2 diabetes mellitus for at least one year, were treated with oral antidiabetic drugs and/or insulin, and had no communication problems. Data were collected using the Participant Intake Form, the Diabetes Burnout Scale and the SF-12 Quality of Life Scale. Data were analyzed using structural equation modeling and mediation effect analysis. Results: Burnout was found to have a direct and negative effect on quality of life (? = -0.460, p < 0.001) and an increase in burnout level decreased quality of life. In addition, burnout had a positive and significant effect on glycemic control (? = 0.118, p < 0.001) and glycemic control had a negative and significant effect on quality of life (? = -0.593, p < 0.001). Glycemic control was found to have a partial mediating role in the relationship between burnout and quality of life. Conclusion: The results of the study suggest that burnout in DM patients has a negative impact on quality of life, both directly and indirectly via glycemic control. Elevated levels of burnout lead to impaired glycemic control and reduced quality of life. Therefore, it is recommended to implement interventions such as psychological support and training to manage burnout in patients with diabetes

Amaç: Bu araştırmanın amacı, Tip 2 Diyabet tanısı almış hastalarda tükenmişlik düzeyinin yaşam kalitesi ve glisemik kontrol üzerindeki etkilerini incelemektir. Özellikle tükenmişliğin hastaların HbA1c düzeyi, kan glikozu kontrolü ve genel sağlık durumlarına yansımasını belirlemek ve tükenmişlik düzeyinin yaşam kalitesi ile ilişkisini değerlendirmek hedeflenmiştir. Gereç ve Yöntem: Araştırma, Ocak-Mart 2024 tarihleri arasında Türkiye'nin doğusunda bir üniversite hastanesinin endokrin servisinde tanımlayıcı ve ilişkisel bir tasarımla yürütülmüştür. Çalışmaya 18 yaş üzeri ve en az 1 yıldır tip 2 DM (Diabetes Mellitus) tanısı almış olan, oral antidiyabetik ve/veya insülin tedavisi alan ve iletişim problemi olmayan 168 hasta dahil edilmiştir. Veriler Katılımcı Tanıtım Formu, Diyabet Tükenmişlik Ölçeği ve SF-12 Yaşam Kalitesi Ölçeği kullanılarak toplanmıştır. Verilerin analizinde yapısal eşitlik modellemesi ve aracılık etkisi analizi kullanılmıştır. Bulgular: Araştırmada tükenmişliğin yaşam kalitesi üzerinde doğrudan ve negatif bir etkisi olduğu (? = -0.460, p < 0.001), tükenmişlik düzeyinin artmasının yaşam kalitesini düşürdüğü belirlenmiştir. Ayrıca tükenmişliğin glisemik kontrol üzerinde pozitif ve anlamlı bir etkisi olduğu (? = 0.118, p < 0.001), glisemik kontrolün de yaşam kalitesi üzerinde negatif ve anlamlı bir etkisi olduğu (? = -0.593, p < 0.001) saptanmıştır. Glisemik kontrolün, tükenmişlik ve yaşam kalitesi arasındaki ilişkide kısmi aracı rolü olduğu tespit edilmiştir. Sonuç: Araştırma bulguları, DM hastalarında tükenmişliğin yaşam kalitesini doğrudan ve glisemik kontrol aracılığıyla dolaylı olarak olumsuz etkilediğini göstermektedir. Artan tükenmişlik düzeyleri, glisemik kontrolün bozulmasına ve yaşam kalitesinin düşmesine yol açmaktadır. Bu nedenle, diyabetli hastalarda tükenmişlikle başa çıkmaya yönelik psikolojik destek ve eğitim gibi müdahalelerin uygulanması önerilmektedir.
Diyabet Tükenmişliği ve Yaşam Kalitesi Arasındaki İlişki: Glisemik Kontrolün Aracı Rolü
Keywords: ?Internal Diseases Nursing?; Dahili Hastalıklar Hemşireliği